Effect of DHA+EPA on oxidative stress and apoptosis induced by ischemia‐reperfusion in rat kidneys. (3rd September 2012) - Ajami, Marjan; Davoodi, Sayed Hossein; Habibey, Rouhollah; Namazi, Nasim; Soleimani, Mansoureh; Pazoki‐Toroudi, Hamidreza
Abstract: Apoptosis, as well as necrosis, has an important role in post‐ischemic renal pathology. The effect of pretreatment with Docosahexaenoic acid+Eicosapentaenoic acid (DHA+EPA) on renal injury and apoptotic protein expression was evaluated. Right nephrectomy was completed on male Wistar rats (255–300 g). The rats received DHA+EPA (200 mg/kg/day) of distilled water orally for 14 days before ischemia reperfusion (IR) or sham operation. A total of 81 rats were divided into three main groups with 6, 24 and 48 h of post‐operation or reperfusion period. Serum creatinine (SCr), BUN, creatinine clearance (CCr) and fractional excretion of sodium (FEN a ) were measured. Tissue levels of malondialdehyde (MDA), superoxide dismutase (SOD) and catalase (CAT) activities, Bax and Bcl‐2 protein expressions and renal histological injury were determined. SCr, BUN and FEN a increased 6–48 h of reperfusion ( P < 0.01). Tissue MDA content and Bax expression increased ( P < 0.01) and CAT and SOD activities decreased ( P < 0.05) in the IR group. DHA+EPA decreased SCr and BUN, FEN a, tissue MDA levels ( P < 0.05 vs. IR) and increased CAT and SOD activities and Bcl‐2 expression ( P < 0.05 vs. IR) for 6–48 h after ischemia. IR induced mild (6 h, P < 0.05) and severe (24–48 h, P < 0.01) tissue damage. Mild‐to‐moderate tissue damage was observed in DHA+EPA groups from 6 to 48 h of reperfusion period ( P < 0.05 vs. IR, 24–48 h). In conclusion, the results suggest that pre‐ischemic exposure to DHA+EPA could improve the outcome of early graft function by inhibition of IR‐induced oxidative stress and apoptosis.